A microstructure-based macro-micro multi-scale fine-blanking simulation of ferrite-cementite steels. (August 2017) - Zhuang, Xincun; Ma, Siming; Zhao, Zhen
Highlights: Macro-micro multi-scale simulation of fine-blanking process was performed. Microstructure-based sub-models were generated for the microscopic simulations. Fine-blanking ability was investigated with microscopic sub-models. Fine-blanking surface quality of ferrite-cementite steels was well predicted. Abstract: The fine-blanking process of ferrite-cementite steels was simulated with a macro-micro multi-scale approach. In the macroscopic simulation, the effects of material and blanking clearance were investigated by evaluating the damage work density of the material in the center of the fine-blanking shearing zone. A series of microstructure-based models with different particle fraction and distribution were generated as sub-models for the microscopic simulations. Microscopic damage in the sub-models was predicted with the damage work model. The simulation results indicated that an increase in particle fraction and the existence of carbide banding accelerated the microscopic damage of the material in the shearing zone during fine-blanking. Micro cracks appeared and extended along the carbide band. In addition, an increase in blanking clearance speeded up the microscopic damage accumulation at the microscale and caused early fracture of the material in the shearing zone at the macro scale. The SEM observations of various fine-blanking specimens substantiated the predictions of the simulations and suggested that severe carbide banding would change the macro crack path in the sheets, adversely affecting the quality of the blanking surface. Graphical abstract: